Comparison between transfer path analysis methods on an electric vehicle. (March 2017) - Diez-Ibarbia, A.; Battarra, M.; Palenzuela, J.; Cervantes, G.; Walsh, S.; De-la-Cruz, M.; Theodossiades, S.; Gagliardini, L.
Abstract: A comparison between transfer path analysis and operational path analysis methods using an electric vehicle is presented in this study. Structure-borne noise paths to the cabin from different engine and suspension points have been considered. To realise these methods, two types of test have been performed; operational tests on a rolling road and hammer tests in static conditions. The main aim of this work is assessing the critical paths which are transmitting the structure-borne vibrations from the electric vehicle's vibration sources to the driver's ear. This assessment includes the analysis of the noise contribution of each path depending on the frequency and vehicle speed range and moreover, the assessment of the path noise impact for harmonic orders which arise due to the physical components of the electric vehicle. Furthermore, the applicability of these methods to electric vehicles is assessed as these techniques have been extensively used for vehicles powered with internal combustion engines.